ANALISIS ANGGARAN SEBAGAI PERENCANAAN DAN PENGENDALIAN BIAYA PRODUKSI PADA PT. PERKEBUNAN NUSANTARA V PABRIK KELAPA SAWIT SEI PAGAR KECAMATAN PERHENTIAN RAJA KABUPATEN KAMPAR - Rhika Selviana; Gusnardi '; Hendripides ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research was conducted at PT. Perkebunan Nusantara V Sei Pagar Kampar regency engaged in oil palm plantations. The purpose of this study is to determine whether the production cost budget serves as good planning and control. In this research the research method used is descriptive method, and data collection is done by direct interview with head of budget department and each part company about company activity and budget implementation at company. The problems encountered in the study are limited to problems in the process of budget preparation as a planning and control of production costs. After doing research, it can be concluded that PT. Perkebunan Nusantara V Sei Pagar Kampar District has used the budget as a planning and controlling production costs in running its business. However, the implementation of the budget has not been able to meet the desired target company because there are still irregularitiesKeywords: Budget Production Cost, Planning, and Control